214k views
2 votes
How to find constant M ? did I do anything wrong here ?

How to find constant M ? did I do anything wrong here ?-example-1
User Anhlc
by
5.6k points

2 Answers

6 votes
Your answer is M=-1 N=-7
User Dmitry Fadeev
by
4.7k points
0 votes

Answer:

M=-1, N=7

Explanation:

Something went wrong on the 4th line.

From the third line, it should read

2x^2-x+6Mx-3M+4

=x(2x-1+6M) - 3M+4

Equating with the RHS,

2x-1+6M = 2x-7

6M = -7+1 = -6

M = -1

Therefore

N = -3M+4 = -3(-1)+4 = 7

or

M=-1, N=7

User New Q Open Wid
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.